Large‑scale water balance indicators for different pruning dates of tropical wine grape - Teixeira, Antônio Heriberto de Castro; Tonietto, Jorge; Leivas, Janice Freitas (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to develop and apply water balance indicators to be scaled up in the wine grape (Vitis vinifera) growing regions of the municipalities of Petrolina and Juazeiro, in the states of Pernambuco and Bahia, respectively, Brazil, simulating different pruning dates along the year. Previous energy balance measurements were used to relate the crop coefficient (Kc) with the accumulated degree‑days (DDac). This model was applied to scale up the water balance indicators during the growing seasons. When irrigation water was available, the best pruning periods were from May to July, due to the better natural thermal and hidrological conditions. More care should be taken for pruning done in other periods of the year, regarding the effect of increasing thermal conditions of wine quality. The water balance indicators, both successfully developed and applied, allow large‑scale analyses of the thermohydrological conditions for wine grape production under the semiarid conditions of the Brazilian Northeast.